ENERGY EFFICIENCY MANAGEMENT OF WATER TRANSPORT VEHICLES THROUGH THE USE OF THERMOSTABLE EPOXY COMPOSITES - Buketov, Andrii; Zhytnyk, Danyl; Totosko, Oleg; Klevtsov, Konstantin; Sharko, Oleksandr (Science-based technologies, 2025)
Polymer composite materials are widely used in water transport in the form of corrosion- and wear-resistant composites. At the same time, scientists are currently conducting a range of research to create materials with improved properties, including thermal properties. The filling of the epoxy matrix with modifying additives is of current interest. The latter are usually physically and chemically active to interact with the macromolecules of epoxy resin, which allows for the creation of a strongly cross-linked structure of a homogeneous system during polymerization. It was believed that the use of 2,4-diaminoazobenzene-4’-carboxylic acid as a modifying additive was promising. Such an additive is characterized by the presence of active groups that can interact with epoxy resin chains at the micro level during the structure formation of materials. This factor ensures the improvement of the thermophysical properties of the developed materials for water transport. In this work, the optimal concentration of the modifier in epoxy resin was determined according to the criteria of thermal characteristics. It has been established that to obtain a composite material with improved thermal properties, it is necessary to add the modifying additive 2,4-diaminoazobenzene-4’-carboxylic acid at a concentration of 0.5-1.5% to the epoxy polymer in the presence of 100% of the epoxy oligomer. This ensures an increase in heat resistance compared to the unfilled epoxy matrix from 342 K to 357-359 K, and the glass transition temperature from 328 K to 344-347 K. It is substantiated that this is due to the intensification of relaxation processes in the developed materials. Also, due to the presence of a modifying additive in the polymer, new chemical and physical bonds between the structural elements of the composite ingredients are formed per unit volume of materials.